Pathogenic variability of Xanthomonas manihotis, the causal agent of cassava bacterial blight - Elango, Fritz; Lozano, J.C. (1981)
Greenhouse studies on pathogenic variability of Xanthomonas manihotis did not reveal the occurrence of distinct pathogenic races. The non-race status of the pathogen suggests that CBB could be well-controlled in the field by using known levels of genotype resistance in specific ecosystems and by programing the planting of cassava according to climatological factors such as rainfall. (AS)